2021
DOI: 10.1016/j.eprac.2021.06.016
|View full text |Cite
|
Sign up to set email alerts
|

Long COVID in Patients With Mild to Moderate Disease: Do Thyroid Function and Autoimmunity Play a Role?

Abstract: Objective Long COVID (LC) is an emerging global health issue. Fatigue is a common feature. Whether thyroid function and autoimmunity play a role is uncertain. We aimed to evaluate the prevalence and predictors of LC and the potential role of thyroid function and autoimmunity in LC. Methods We included consecutive adults without known thyroid disorder, admitted to a major COVID-19 centre for confirmed COVID-19 from July to December 2020 who had thyroid function tests (TF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
40
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 43 publications
(44 citation statements)
references
References 33 publications
4
40
0
Order By: Relevance
“…Our institution, Queen Mary Hospital, is one of the major centers in Hong Kong receiving confirmed COVID-19 patients. Consecutive adult patients (aged ≥18 years) admitted to Queen Mary Hospital for COVID-19 between 21 July 2020 and 20 April 2021 were prospectively recruited ( 12 , 18 , 19 ). The presence of SARS-CoV-2 was confirmed in all patients by RT-PCR from the nasopharyngeal swab (NPS) and/or deep throat saliva (DTS), using the LightMix SarbecoV E-gene assay (TIB Molbiol, Berlin, Germany) which targeted the envelope protein (E) gene of SARS-CoV-2 as we described previously ( 20 ).…”
Section: Methodsmentioning
confidence: 99%
“…Our institution, Queen Mary Hospital, is one of the major centers in Hong Kong receiving confirmed COVID-19 patients. Consecutive adult patients (aged ≥18 years) admitted to Queen Mary Hospital for COVID-19 between 21 July 2020 and 20 April 2021 were prospectively recruited ( 12 , 18 , 19 ). The presence of SARS-CoV-2 was confirmed in all patients by RT-PCR from the nasopharyngeal swab (NPS) and/or deep throat saliva (DTS), using the LightMix SarbecoV E-gene assay (TIB Molbiol, Berlin, Germany) which targeted the envelope protein (E) gene of SARS-CoV-2 as we described previously ( 20 ).…”
Section: Methodsmentioning
confidence: 99%
“…Our previous publication has demonstrated that characteristics of COVID-19 patients admitted to Queen Mary Hospital were largely similar to those admitted to other centres in Hong Kong. Hence, our cohort is representative of COVID-19 patients in Hong Kong [13] . Consecutive adult patients (aged ≥18 years) admitted to Queen Mary Hospital for COVID-19 between 21 July 2020 and 20 May 2021 were prospectively recruited.…”
Section: Methodsmentioning
confidence: 99%
“…However, further studies with more sample size and lengthy follow-up are required to give a fine conclusion. 61 Furthermore, a recent case-control study found a significant correlation between hypothyroidism and prolonged SARS-CoV-2-induced anosmia and suggested that the smell dysfunction is likely due to the direct virusinduced damage on both the thyroid and olfactory nerve. 62 Moreover, this no olfactory function or slow recovery is likely because of viral-induced thyroid damage resulting in depletion of thyroid hormones may impair the regeneration and maturation of olfactory neural cells at least in a subset of cases with thyroid dysfunction.…”
Section: Long-covid: Thyroid Gland and Autoimmunitymentioning
confidence: 99%
“…However, further studies with more sample size and lengthy follow-up are required to give a fine conclusion. 61 …”
Section: Long-covid: Thyroid Gland and Autoimmunitymentioning
confidence: 99%